HUBUNGAN PEMBERIAN APRESIASI TERHADAP MINAT BELAJAR IPS SISWA KELAS VII DI SMP NEGERI 1 X KOTO DIATAS - lidya elviana; Gustia Sainanda; Merika Setiawati (Universitas Labuhanbatu, 2022)
This research was motivated by the lack of studets interest in participating in social science learning and the lack of appreciation from the teacher in appreciating students efforts to participate in teaching and learning activities. The aims of this study were (1) to find out whether there is a relationship between giving appreciation to the interest in learning of class VII student of SMP Negeri 1 Koto Diatas. (2) Knowing the magnitude of the relationship of appreciation to the learning interest of class VII student of SMP Negeri 1 X Koto Diatas. This type of research is a quantitative research with a sample of all students of class VII student of SMP Negeri 1 X Koto Diatas as many as 31 students. Data collection techniques using questionnaires and data analysis techniques using product moment correlation techniques. The results of this study are that there is a positive and significant relationship between giving appreciation to the learning interest of class VII student of SMP Negeri 1 X Koto Diatas. This is evidenced from the results of the analysis obtained that rcount = 0,512 is greater than rtable (sig. 5% for N = 31) which is 0,355 and the correlation test result is 0,6, it is stated that the relationship between appreciation variables and interest in learning is quite strong.Keywords: Appreciation, Interest, and Learning.